Synthesis of carbon nanotubes (CNTs) using Cobalt/Zinc Oxide as a floated catalyst precursor and palm oil as a carbon precursor / Nurul Hasnida Dahalan - Dahalan, Nurul Hasnida (2012)
Vertically aligned carbon nanotubes (VACNTs) have been synthesized in a thermal catalytic chemical vapor reactor using natural palm oil as the carbon source. The main motivation of the used natural palm oil as the carbon precursor because to provide "green" alternatives of cheap and renewable raw materials for CNT production The growth of vertically aligned CNTs nanostructures will be prepared at different temperature and molarity. To get the image of the CNTs produced by same method but different parameters we characterized it with Field Emission Scanning Electron Microscope (FE-SEM) and also determine the Raman Spectra by the Raman Spectroscope (RS) characterization. Futhermore, we also the FTIR spectrum using Fourier Transform Infra Red Spectroscopy (FTIR). Based on this research, the optimize temperature to produce vertically aligned CNTs is 800°C. While for the effect of the bimetal Cobalt/Zinc Oxide catalyst, the optimize molarity of Zinc Oxide is 0.15 mol